Gender Differences in the Distribution of Total Work-Time of Latin-American Families: The Importance of Social Norms - Juan Carlos Campa\~na; J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute for the Study of Labor (IZA), 2015)
We analyze differences by gender in the time dedicated to total work (paid and unpaid) by families in Latin America, with particular attention to the effect of social norms. To this end, we use survey data on time use in Mexico (2009), Peru (2010), Ecuador (2012) and Colombia (2012), to estimate differential equations through OLS. Our results reveal differences between countries in terms of the gender distribution of total work (paid work plus unpaid work), with Colombia and Peru being more equitable. These two countries could be approaching a situation of "iso-work", or equality of work, in the sense that men and women spend similar amounts of time in total work. When considering the social norms that explain gender differences in the time spent in total work, we use data from the last wave (2010-2014) of the World Values Survey (WVS). Our results indicate that the more egalitarian countries exhibit the highest levels of equality in the distribution of work. It is important to know how men and women from these four countries distribute their time in total work, in order to understand why there are clear differences by gender.
Keywords: D13; J22; J13; J16; 330; total work; Latin America; differences by gender; social norms